(untitled) (Veterinária Notícias, 2021)
For development of techniques aimed on increasing sperm longevity, it is necessary the understanding of this cell metabolism. The sperm requires a constant supply of energy to maintenance of cell functions. Approximately 500 metabolic reactions are known to occur in somatic cells, and many of them require energy. To achieve its goal, most of produced energy is destined for sperm motility, which is a specialized process and ATP-dependent. The sperm has the necessary mechanisms to produce energy through glycolysis, citric acid cycle (Krebs cycle) and Oxidative Phosphorylation. Understanding these pathways is necessary to know the interactions between the semen extender substrates and sperm cells. The aim of this review is to approach the major energy production pathways of sperm, as well as the substrates available for this metabolism.